BIOLOGICAL REFERENCE POINTS OF PAINTED SPINY LOBSTER Panulirus versicolor (Latreille, 1804) IN KARIMUNJAWA WATERS, INDONESIA - Tri Ernawati; Asep Priatna; Fayakun Satria (Indonesian Fisheries Research Journal, 2019)
A biological reference point is a term used to explain of stock status using a biological approach as a basic of fisheries management. Biological reference points of painted spiny lobster Panulirus versicolor are limited in Karimunjawa waters. This study aims to investigate the stock status of P. versicolor and management options to ensure the sustainability of the resources. The research was conducted in Karimunjawa islands of the Java Sea by collecting lobster from local fishers from March to November 2016. A total of 495 lobster were measured, weighed, and their maturity status assessed to allow the size at maturity and selectivity of the fishery to be estimated. The size at maturity L50 (62.2 mm CL) and L95 (82.0 mm CL) were larger than SL50 (48.2 mm CL) and SL95 (75.0 mm CL), respectively. Natural mortality (M) which was 0.579 year-1 is lower than fishing mortality (F). The current spawning potential ratio (SPR) of P. versicolor is 19% at the current F of 0.82, which is below SPR limit of 20% and target reference point of 40%. Hence, to increase SPR level to 40%, the fishing mortality should be reduced by about 40% to 60%. Closed season, legal size, and defining no take zone are options to consider by fishery manager with appropriate surveillance control. Single or combining those measures can reduce its fishing mortality and take back the stocks to the level of target reference point.